Teachers' Perceptions of Self-Determination among Deaf / Hard of Hearing Students - Aboalola, Nawal Ahmad (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: This study aims to assess the level of self-determination skills acquired by deaf and hard of hearing students (HISs) as perceived by their teachers. And to examine whether their levels differ due to variations in severity, type of disability, students’ age, or teachers’ years of experience as independent variables. The dependent variable is the level of self-determination skills. Methods: A descriptive-analytical method was used. The study sample consisted of 90 teachers who responded to a self-determination skills questionnaire. The data were analyzed with descriptive statistics through averages, standard deviations, relative weight, the Kruskal–Wallis test, and the Mann–Whitney test to validate the study hypotheses. Results: The findings revealed that HISs acquired a high level of self-determination skills in their teachers’ views (M = 3.638, RW = 72.8%). In addition, there were significant differences in the level of self-determination skills acquired by HISs in relation to disability severity and the students’ ages. On the other hand, no significant differences were detected according to the type of disability or the teachers’ years of experience. Independent variables significantly contribute to determining the level of self-determination skills in the deaf and hard of hearing. Conclusion: The study's findings present empirical evidence indicating the feasibility of improving self-determination skills for the hearing impaired and suggest further studies.